Exploring Student Perceptions of Virtual Learning Experiences: A Study of the Use of the Spatial.io 3D Metaverse Platform - Rudi Susilana; Laksmi Dewi; Rullyana, Gema (Journal of Education Technology, 2024)
The advancement of virtual reality technology, such as metaverse, has attracted attention as a transformative innovation. This study was motivated by the lack of in-depth understanding of the use of virtual technology by students and their perceptions of the learning experience through the Spatial.io platform. The Spatial.io platform offers new opportunities to improve the quality of online learning in higher education. The Educational Technology Study Program developed a virtual learning space using the Spatial.io 3D metaverse platform. This study aims to explore students' perceptions of virtual learning through the platform and understand how to utilize this innovative learning space for academic purposes. A quantitative descriptive approach with a survey research design was used in this study, involving 82 students. Data collection was carried out using a questionnaire that measured six aspects of students' perceptions of immersive learning, namely Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Perceived Satisfaction (PS), Interactivity (INT), Virtual Environment (VE), and Learning Experience (LE). Data analysis techniques used qualitative and quantitative descriptive. The results showed that students positively perceived virtual learning through the Spatial.io 3D Metaverse platform. These findings underscore the technology's enormous potential in improving the quality of online learning, particularly in higher education.